Pore Hierarchy in Mesoporous Silicas Evidenced by In-Situ SANS during Nitrogen Physisorption. - Thommes, Matthias; et al. (Langmuir, 2007)
The pore hierarchy of a hierarchical porous SiO2 with 14 nm spherical mesopores and 3 nm worm-like pores (KLE1C16) is studied by small-angle neutron scattering (SANS) in combination with in-situ nitrogen sorption at 77 K. A novel setup is used developed at Hahn-Meitner Institute, Berlin. It is demonstrated that in these materials indeed all of the large mesopores are connected through the smaller ones, thus providing invaluable insights into the general phenomenon of pore connectivity in mesoporous materials. [on SciFinder(R)]
Keywords: pore hierarchy mesoporous silica SANS nitrogen physisorption